Corrigendum to: Enhanced Long-term Stability and Carbon Resistance of Ni/MnxOy-Al2O3 Catalyst in Near-equilibrium CO2 Reforming of Methane for Syngas Production [15(2), 2020, 331-347] - Baya Djebarri; Fouzia Touahra; Nadia Aider; Ferroudja Bali; Moussa Sehailia; Redouane Chebout; Khaldoun Bachari; Djamila Halliche (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
According to Authors request (10th December 2020), Corrigendum to: Djebarri, B., Touahra, F., Aider, N., Bali, F., Sehailia, M., Chebout, R., Bachari, K., Halliche, D. (2020). Bulletin of Chemical Reaction Engineering & Catalysis, 15(2), 2020, 331-347 (doi:10.9767/bcrec.15.2.6983.331-347). First Author (Baya Djebarri) is added as member of Corresponding Author because of his largest contribution in the article and his expertise.Correction:The Authors Names were corrected to:Baya Djebarri1,*, Fouzia Touahra2,*, Nadia Aider4, Ferroudja Bali3, Moussa Sehailia2, Redouane Chebout2, Khaldoun Bachari2, Djamila Halliche3 The information detail of Corresponding Authors was corrected to:* Corresponding Authors.   Email: tfafaze256@yahoo.fr (F. Touahra); b.djebarri@univ-boumerdes.dz (B. Djebarri)Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).